Application of lacrimal gland ultrasonography in the evaluation of chronic ocular graft-versus-host-disease - Zhong, Mingxia; Liu, Siyuan; Luo, Jinghan; Zhang, Qin; Yang, Zhou; Zhang, Shanshan (Frontiers in Immunology, 2025)
ObjectiveTo investigate the effectiveness of lacrimal gland ultrasonography in the assessment of chronic ocular graft-versus-host-disease (oGVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and to establish the correlation between the ocular surface and ultrasonographic results.MethodThe cross-sectional study included 57 participants aged 18 and older, who were at least 100 days after allo-HSCT. The study was conducted at the oGVHD clinic of Peking University People’s Hospital between March to June 2023. Patients were categorized into groups according to the International Chronic oGVHD (ICCGVHD) consensus group diagnostic criteria or the 2005 National Institutes of Health (NIH) classification criteria for Chronic GVHD. Demographics and transplantation-related information were collected for all participants, including age, gender, donor-recipient HLA matching, donor-recipient ABO matching, donor-recipient gender combination and duration after allo-HSCT. The disease activity of oGVHD and the severity of ocular surface involvement were assessed using various parameters such as Ocular Surface Disease Index (OSDI), Schirmer test, tear film break-up time (BUT), tear meniscus height, corneal/conjunctival staining and meibomian gland dropout. Lacrimal gland structures were assessed by B-mode and Doppler ultrasonography to measure parameters such as the long diameter, thick diameter, homogeneity and parenchymal vascularization. Statistical analyses were performed to determine differences in ocular surface conditions and lacrimal gland ultrasonographic parameters between groups as well as to determine the correlation between ocular surface condition and lacrimal gland ultrasonographic findings.Result(1) Patients with definite and probable oGVHD exhibited a significantly longer duration after allo-HSCT compared to non-oGVHD patients (H=11.264, p<0.01), The median durations were 247(164,894) days and 525(310,928) days, respectively, compared to 204(169,323.25) days for non-oGVHD patients. (2) Compared to non-oGVHD patients, both definite oGVHD patients and probable oGVHD patients showed lower average of Schirmer test (H=31.188, p<0.01), TBUT (H=11.853, p<0.01), tear meniscus height (H=13.630, p<0.01) and higher average of OSDI (F=27.992, p<0.01), corneal staining scores (χ²=23.66, p<0.05) and temporal conjunctival staining scores (χ²=14.84, p<0.05). (3) The B-mode and Doppler ultrasonography parameters in lacrimal glands including long diameter, thick diameter, homogeneity and parenchymal vascularization did not exhibit significant differences between the three groups. (4) The long diameter in lacrimal ultrasonography had significantly positive correlations with tear meniscus height (r=0.297, p<0.05) and significantly negative correlations with temporal conjunctival staining scores (r=-0.313, p<0.05) and staining total scores (r=-0.285, p<0.05). The thick diameter in lacrimal ultrasonography demonstrated significantly positive correlations with tear meniscus height (r=0.404, p<0.01), and significantly negative correlations with OSDI (r=-0.273, p<0.05), corneal staining scores (r=-0.264, p<0.05), nasal conjunctival staining scores (r=-0.271, p<0.05) and staining total scores (r=-0.312, p<0.05). Homogeneity and parenchymal vascularization were not found to be significantly correlated with ocular surface status.ConclusionThe ocular surface condition in oGVHD patients is worse than that observed in non-GVHD patients. The main manifestations include keratoconjunctival injury and a reduction in tear secretion and tear film stability. These effects appear to be a common result of chemoradiotherapy-induced inflammation and rejection-associated responses. There were no significant differences in the morphology of lacrimal glands as revealed by ultrasonography. This suggests that ocular rejection may not be the primary cause of lacrimal gland changes in oGVHD patients. While ultrasonography can provide insight into tear secretion, its efficacy in diagnosing oGVHD appears limited.